AWAY WITH THE PENGUINS - Prior, Hazel (London : Black Swam an in imprint of Transworld Publishers, 2020)
Veronica McCreedy is about to have the journey of a lifetime . . . Veronica McCreedy lives in a mansion by the sea. She loves a nice cup of Darjeeling tea whilst watching a good wildlife documentary. And she's never seen without her ruby-red lipstick. Although these days Veronica is rarely seen by anyone because, at 85, her days are spent mostly at home, alone. She can be found either collecting litter from the beach ('people who litter the countryside should be shot'), trying to locate her glasses ('someone must have moved them') or shouting instructions to her assistant, Eileen ('Eileen, door!'). Veronica doesn't have family or friends nearby. Not that she knows about, anyway . . . And she has no idea where she's going to leave her considerable wealth when she dies. But today . . . today Veronica is going to make a decision that will change all of this. Readers love Hazel Prior! 'Oh I so adored this beautiful, unique book!' 'A complete pleasure from start to finish.' 'A touching, absorbing and uplifting story.' 'Tender, heartwarming and sensitively written.
"Granny McCreedy's about to go on the journey of a lifetime..." -- Cover.
Keywords: Older women -- Scotland -- Fiction; Fiction Recluses -- Fiction; Rich people -- Fiction; Inheritance and succession -- Fiction; Intergenerational relations -- Fiction; Humorous fiction; Domestic fiction